Rękojmia za wady w świetle art. 27 ustawy o ochronie praw nabywcy lokalu mieszkalnego lub domu jednorodzinnego — wybrane zagadnienia - Kułak, Krzysztof (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The subject of the article are the main issues regarding a developer’s liability for defects of aflat or a single-family house under the warranty for defects and under the provisions of the act on the protection of the rights of a flat or a single-family house purchaser. The analysis includes the legal nature of the reference in art. 27 al. 6 of “the development act”, the mutual relations of the provisions of the Civil code on warranty for defects and the provisions of art. 27 al. 1–5 of “the development act”, as well as the issue of applying art. 557 § 1 of the Civil code. The article proposes an interpretation of these provisions that reconciles their wording with the objective of “the development act” which is to protect the purchaser’s rights.
Keywords: development agreement; development act; developer; purchaser; flat; single-family house; physical defect; legal defect; acceptance report; defect removal; contract renunciation; price reduction; warranty for defects; acceptance; defect